Strengthening Governance and Innovative Work Behavior through Training and Mentoring at BUMDes Mandala Sari, Bongkasa Pertiwi Village, Abiansemal District, Badung Regency, Bali Province - Surya, Ida Bagus Ketut; Riana, I Gede; Dana, I Made; Sudirman, I Made Surya Negara; Suparna, Gede; Mandala, Kastawan; Dhan, Ni Kadek Sari Jayanti; Dewi, Desak Made Pradnya (PT. Global World Scientific, 2025)
Village-owned enterprises (BUMDes) are village economic institutions that aim to optimize local potential through participatory and professional business management. In Bali Province, the existence of more than 600 BUMDes reflects the strategic role of this institution in village economic development. However, several challenges, such as weak human resource capacity, suboptimal financial governance, and low innovation, are significant obstacles. The case of BUMDes Mandala Sari in Bongkasa Pertiwi Village reflects this problem, with a decline in turnover during 2019–2022 due to the pandemic and lack of managerial innovation. This condition encouraged the involvement of the Udayana University Community Service Team to implement training and mentoring programs based on innovative work behaviour. The program implemented includes basic accounting training, application-based financial management, and innovative work behaviour counselling designed to strengthen the competitiveness of BUMDes. Mentoring was carried out during the Udayana University KKN period, involving lecturers and students to ensure that implementation runs sustainably. The results show increased accounting knowledge, managerial skills, and innovative awareness among BUMDes administrators and employees. This program is expected to become a BUMDes development model that can be replicated in other villages, especially in the digital era and changing market dynamics. Integrating work innovation and financial transparency is the key to building a competitive, professional, and sustainable BUMDes.